Peran Keluarga untuk Mencegah Penularan TB Paru dalam Keluarga Di Wilayah Kerja Puskesmas Gajah Demak - Indah Puspitasari; Ana Zumrotun Nisak; Yayuk Mundriyastutik (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2021)
According to the health profile of Demak, the number of TB in Gajah health center ranks 6th out of 20 places. Total cases is 924 sufferes, with the number of BTA+ patients as a whole as many as 516 patients. In doing disease prevention efforts not only be done by the client itself or health workers alone but also play a role, so it takes the role of family to prevent the occurrence of transmission of pulmonary TB disease in the working area of Gajah Health Center Demak District. This research uses qualitative method with case study approach. The purpose of this research is to knowing deeply the five roles of family in knowing, deciding, taking care, modifying environment and utilizing health facility to prevent transmission of pulmonary TB disease in working area of Gajah Health Center of Demak Regency.From the results of this study, most of the informants did not know about the understanding of TB disease but, in general the role of the family to prevent transmission of pulmonary TB was good enough, although it was still not optimal because, there were still a number of efforts to prevent TB transmission that were not done by the family. For example, families do not understand the duties and functions of PMO, do not separate the use of eating utensils with patients pulmonary TB, and do not pay attention to the importance of reminding people with pulmonary TB when coughing. Suggestion of this research result for Puskesmas Gajah of Demak Regency in order to add and modify program of Lung TB prevention. In addition to regular monitoring or regular home visits to monitor the treatment and prevention of TB transmission done by the family at home.